Poverty alleviation of destitute women and poor farmers in Barisal district of Bangladesh through beef fattening - Amin, Mohammad Rohul; Rahman, Mohammad Hafizur; Talukder, Milton; Asgar, Md Ali; Paul, Ashit Kumar; Mollah, Mohammad Lalmoddin (Asian Journal of Medical and Biological Research, 2016)
<!–[if gte mso 9]> ismail - [2010] 11.5606 <![endif]–> The cattle fattening programme was represents an important component of the agribusiness sector with great economic, income, poverty alleviation and social implications. The present study was performed at Barisal district in Bangladesh. Data were collected from 220 women and farmers on their household during the period June, 2013. Among them, 54 destitute women and poor farmers were identified and making groups of them for beef fattening. 54 cattle of each destitute women and poor farmers were randomly divided into nine groups (A, B, C, D, E, F, G, H and I), each consisting of six (6) cattle. Endex®, Aldazole® and Tetranid® were administered orally to the cattle of group A, B and C, respectively. Cattle of group D received subcutaneously Oxynil®. Cattle of group E received orally Peraclear® and Urea Molasses Straw (UMS). Cattle of group F received orally Endex® and lugols iodine intravenously. Cattle of group G were treated orally with Endex® and Metaphos® intramuscularly. Cattle of group H were treated orally with Endex® and A-Sol® intramuscularly. Cattle of group I was kept as control without giving any treatment. Body weight was examined before trials (day 0) and on 10th day, 20th day, 30th day, 40th day, 50th day, 60th day and 70th day. Out of the 220 women and farmers 56.36% were involved in agriculture, 10.45% in own business, 3.64% in shared business, 6.36% in govt. service and 23.18% in non-govt. service. 18.18% women and farmers had the knowledge of animals characteristics used for beef fattening. The knowledge of feed, animal diseases, veterinary drugs, animal vaccine, and drugs used for beef fattening was 18.64%, 47.73%, 25.45%, 25.45%, and 19.55%, respectively. About 7.73% respondents have training on cattle fattening. The body weight was increased significantly (p<0.01 and p<0.05) after Endex®, Aldazole®, Tetranid®, Oxynil®, Peraclear®+UMS, Endex®+loguls iodine, Endex®+Metaphos® and Endex®+A-Sol® treatment in group A, B, C, D, E, F, G and H, respectively. Highest percentages of body weight gain in Endex® + Metaphos® (19.79%) treated cattle followed by Endex®+A-Sol® (10.06%), Peraclear® +UMS (9.97%) and Endex®+loguls iodine (8.68%) treated cattle. The results of the present study will be helpful for farmers and researchers for beef fattening in Bangladesh. Asian J. Med. Biol. Res. March 2016, 2(1): 48-54 <!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–>